ADITIVOS POLIMÉRICOS COMO FATOR DE PROTEÇÃO E REABILITAÇÃO DE FLUIDOS HIDROARGILOSOS - Amorim, L. V.; Pereira, E.; Gomes, C. M.; Farias, K. V.; Barbosa, M. I. R.; França, K. B.; Lira, H. L.; Ferreira, H. C. (Águas Subterrâneas, 2003)
Indisponível